Seloko Sebagai Media Komunikasi Dakwah Masyarakat Desa Limbur Merangin Kecamatan Pamenang Barat Kabupaten Merangin - Khoirun Nasbih; Dian Mursyidah; Nurbaiti; Zulqarnin (Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2020)
This research is motivated by the reality that occurs in society, namely between people in rural areas who are still implementing seloko, on the contrary in urban areas seloko has begun to fade so that both its existence and value that should be embedded in the identity of the community actually happens the other way around. The research approach that the author uses is a qualitative approach with a descriptive type of research. Research with descriptive theory is a systematic description of the theory and research results that are relevant to the variables to be studied. To obtain accurate and relevant data with the object of research, the authors apply three methods of data collection, namely, field observations, interviews, and documentation. The results obtained by the author are first, da'wah communication using seloko is considered effective because it can make the communicants become interested and feel comfortable, besides that it also makes the substance of the information conveyed more easily understood by the communicants. Second, da'wah communication with seloko is also useful, because the content of seloko itself contains expressions that include rules for behavior in the daily life of the people and legal rules or norms, which are always obeyed and respected by the community because they have sanctions. Applying the substance of the seloko means applying the customs that apply in their respective regions.